7th Forum on New Materials - Part A 2016
DOI: 10.4028/www.scientific.net/ast.97.141
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Superelastic Properties of Au-51Ti-18Co Biomedical Shape Memory Alloy Heat-Treated at 1173 K to 1373 K

Abstract: The effect of heat treatment temperature from 1173 K to 1373 K for 3.6 ks on mechanical and superelastic properties of an Ni-free Au-51Ti-18Co alloy (mol%) was investigated. The stress for inducing martensitic transformation (SIMT) and the critical stress for slip deformation (CSS) slightly decrease with increasing the heat–treatment temperature. Regardless of heat–treatment temperature, good superelasticity was definitely recognized with the maximum shape recovery ratio up to 95 % and 4 % superelastic shape r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Regardless of the heat-treated temperature, B2 parent and B19 martensite phases coexisted in all the heat-treated conditions. The trace of AuTi 3 (L1 2 ) phase which was observed in the Ti-rich AuTi-18Co alloys [8] was not confirmed by XRD analysis. By utilizing the XRD patterns, precise lattice parameters of B2 parent and B19 martensite phase in the all specimens were calculated and they were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Regardless of the heat-treated temperature, B2 parent and B19 martensite phases coexisted in all the heat-treated conditions. The trace of AuTi 3 (L1 2 ) phase which was observed in the Ti-rich AuTi-18Co alloys [8] was not confirmed by XRD analysis. By utilizing the XRD patterns, precise lattice parameters of B2 parent and B19 martensite phase in the all specimens were calculated and they were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 81%
“…AuTi possesses a thermoelastic martensitic transformation from B2 parent phase to B19 martensite phase at around 880 K [5][6][7]. Recently, we found that martensitic transformation temperature of AuTi is lowered to the body temperature by 18 mol% Co addition and superelasticity with shape recovery strain of 3.7 % is obtained at room temperature in the Au-51Ti-18Co alloy heat-treated at 1173 K for 3.6 ks [8]. It is well known that martensitic transformation temperature and shape memory properties are affected by the presence of precipitates after heat-treatment in many alloy systems.…”
Section: Introductionmentioning
confidence: 95%